Computational and Statistical Analysis of Protein Mass Spectrometry Data - Noble, William Stafford; MacCoss, Michael J. (PLOS Computational Biology, 2012)
High-throughput proteomics experiments involving tandem mass spectrometry produce large volumes of complex data that require sophisticated computational analyses. As such, the field offers many challenges for computational biologists. In this article, we briefly introduce some of the core computational and statistical problems in the field and then describe a variety of outstanding problems that readers of PLoS Computational Biology might be able to help solve.